Cassava in tropical Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Cassava in tropical Atrica; a reference manual produced by the International Institute of Tropical Agriculture, 1990 176pp, ISBN 978 131 041 3 Pbk IITA, PNB 5320 Oyo Road, Ibadan, NIGERIA